Legal Measure in Increasing Birth Rate Promotion - Keawphang, Sattra (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objective of the research is to suggest and develop the law to solve problems related to legal measure in increasing birth rate promotion. This research is based on a qualitative research and analysis from documents as follows: The study included a study of documents, concepts and theories as a basis for research from both primary and secondary sources, for example, concepts, theories and laws related to protect children and youth from cyber bullying, were analyzed and studied from books, textbooks, research reports, theses, using the library and library databases in Thai and foreign languages.           In this study, it was found that 1) law in increasing birth rate promotion has been enforced for a long time, the provision related to these are inappropriate with current circumstances; 2) there is a problem of the lack of a primary agency directly responsible related in increasing birth rate promotion.           The authors suggest that amendments in Labour Protection Act B.E. 2541, National Education Act B.E. 2542 (1999), Child Protection Act, B.E. 2546 (2003), Prime Minister's Office Regulations Concerning Leave of Absence for Government Officials B.E. 2555 (2012) and related laws shall include changes related to children must receive an education while working and children cannot work during school hours, free education up to the bachelor's degree level, and educational institutions should be prohibited from charging any fees including free breakfast and lunch arrangement in school, establishing a childcare center for working parents with minimal or no cost, paid maternity leave for one year and father took leave to raise his child for one year.